Oncologic Outcome and Efficacy of Chemotherapy in Colorectal Cancer Patients Aged 80 Years or Older - Liu, Wenting; Zhang, Mengyuan; Wu, Jun; Tang, Ran; Hu, Liqun (Frontiers in Medicine, 2020)
Purpose: The present study aimed to evaluate the oncologic outcomes of patients aged 80 years or older compared with younger patients, and we then further investigated the efficacy of chemotherapy in individuals aged 80 years or older. Methods: A retrospective analysis was conducted using the Surveillance, Epidemiology and End Results (SEER) database. The χ2 test was used to analyze the different clinicopathologic and demographic variables between 65-79 years and ≥ 80 years groups. Kaplan–Meier analysis and log-rank testing were used to compare colorectal cancer-specific survival (CCSS) curves between different groups. Multivariate and univariate Cox proportional hazards models with hazard ratios (HRs) and 95% confidence intervals (CIs) were also used to assess CCSS and OS. Results: A total of 189926 patients were included into our study. Compared with 65-79 years old patients, individuals aged 80 years or older were associated with 48.4% increased colorectal cancer-specific mortality (HR = 1.484, 95%CI =1.453-1.516, P < 0.0001; using 65-79 years old as the reference). Moreover, not receiving chemotherapy was significantly associated with an increased risk of colorectal cancer-related death, independent of other prognostic factors (HR = 0.615, 95%CI = 0.589-0.643, P < 0.0001) in individuals aged 80 years or older. Conclusions: This large population-based study showed that older patients were associated with worse oncologic outcomes compared to younger ones. Chemotherapy could offer survival benefit for very old patients diagnosed with CRC and we strongly believed that very old patients were under-treated in the present medical practices.